Pengaruh Kompetensi dan Motivasi terhadap Kinerja Pegawai pada Dinas Kesehatan Kabupaten Demak - Ernawati Ernawati; Henry Yuliamir (Mahesa Research Center, 2026)
This article aims to conduct an in-depth analysis of the influence of competence and motivation on employee performance at the Demak Regency Health Office. The study is based on the issue of employee performance achievements that have not yet reached optimal levels, which are suspected to be influenced by individual work abilities and varying levels of motivation. This condition calls for an empirical investigation to identify the factors that directly contribute to improving employee work effectiveness. The research employs a quantitative approach by distributing questionnaires to 129 respondents who are active employees at the Health Office. The data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression to examine the effect of each variable. The findings indicate that competence and motivation have a significant influence on employee performance, with motivation emerging as the strongest contributing factor. The research model explains 76.6% of the variation in performance, demonstrating that both variables play an important role in enhancing work performance. These findings emphasize that improving competence through structured training and strengthening motivation through rewards, work support, and continuous coaching are effective strategies to optimize employee performance and improve the quality of public health services at the regional level.